Unveiling Lower-Class Bodies and Queering Labour History: ‘Industrial Sexuality’ - Claire Savina (Gender a Výzkum)
Review of book Hammad, H. 2016. Industrial Sexuality: Gender, Urbanization, and Social Transformation in Egypt. Austin: University of Texas Press.